5G Heterogeneous Networks Self-organizing and Optimization - Rong, Bo.; Qiu, Xuesong; Kadoch, Michel; Sun, Songlin; Li, Wenjing; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This SpringerBrief provides state-of-the-art technical reviews on self-organizing and optimization in 5G systems. It covers the latest research results from physical-layer channel modeling to software defined network (SDN) architecture. This book focuses on the cutting-edge wireless technologies such as heterogeneous networks (HetNets), self-organizing network (SON), smart low power node (LPN), 3D-MIMO, and more. It will help researchers from both the academic and industrial worlds to better understand the technical momentum of 5G key technologies.
Adaptive SON and Smart LPN for 5G Heterogeneous Networks -- Intelligent SDN and NFV for 5G HetNet Dynamics -- Massive MIMO Coordination in 5G Heterogeneous Networks -- Conclusion and Future Research Directions.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks